Pan Africa Bean Research Alliance Model - Buruchara, Robin Arani; Chirwa, Rowland; Abang, Mathew M.; Rubyogo, Jean-Claude (Pan-Africa Bean Research Alliance, 2012)
The Pan Africa Bean Research Alliance is a consortium of African-owned regional bean networks consisting of National Agricultural Research Systems (NARS) from 28 countries in sub- Saharan Africa, the International Center for Tropical Agriculture (CIAT) and a number of donor organizations. PABRA’s focus is to improve bean productivity, utilization and commercialization for the benefit of the urban and rural poor. The ultimate goal is to enhance food security, income generation and health of poor communities in a gender equitable manner. The regional bean networks are Eastern and Central Africa Bean Research Network (ECABREN) covering 9 countries, Southern Africa Bean Research Network (SABRN), covering 11 countries and the West and Central Africa Bean Research Network (WECABREN), covering 10 countries. ECABREN, SABRN and WECABREN are semi-autonomous and respond to priorities defined by corresponding sub-regional organizations, which are ASARECA, SADC/FANR and CORAF/WECARD, respectively. All networks implement the same log-frame under PABRA. Activities in the PABRA workplan are developed using a bottom-up approach, and build on the outcome of national program planning followed by planning at the regional network level. PABRA facilitates collaborative research within, among and beyond the regional networks. It also provides a forum for building and maintaining linkages to multiple partners. These collaborative linkages are maintained and strengthened through joint priority-setting, planning, agreed division of responsibilities, joint implementation of activities, and joint reporting. Collaboration is based on national members’ interest and on comparative advantage. In this way, research technologies are shared among countries and significantly contribute to scaling up and wider distribution efforts. Through this partnership, PABRA facilitated seed access to 7.5 million farmers between 2003-2008 and about 7 million between 2009-2011.